1990
DOI: 10.1073/pnas.87.16.6146
|View full text |Cite
|
Sign up to set email alerts
|

Preferential utilization of conserved immunoglobulin heavy chain variable gene segments during human fetal life.

Abstract: The ability to respond to specific antigens develops in a programmed fashion. Although the antibody repertoire in adults is presumably generated by stochastic combinatorial joining of rearranged heavy variable, diversity, andjoining (VH-DH-JH) and light (VL-JL) chains, experimental evidence in the mouse has shown nonrandom utilization of variable gene segments during ontogeny and in response to specific antigens. In this study, we have performed sequence analysis of 104-day human fetal liver-derived, randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
146
4
1

Year Published

1992
1992
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(162 citation statements)
references
References 40 publications
11
146
4
1
Order By: Relevance
“…Three distinct characteristics of the fetal repertoire have been described, namely restriction in Ag specificities, low avidity, and multireactivity to self Ags. Previous reports have indicated that restrictions in Ag specificities are achieved by limited and preferential usage of certain V H and V gene segments (12,28). Preferential gene use reflected the proximity of gene segments in chromosomal position (8,9,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three distinct characteristics of the fetal repertoire have been described, namely restriction in Ag specificities, low avidity, and multireactivity to self Ags. Previous reports have indicated that restrictions in Ag specificities are achieved by limited and preferential usage of certain V H and V gene segments (12,28). Preferential gene use reflected the proximity of gene segments in chromosomal position (8,9,12).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of V H and V gene expression in different stages of development, in both humans and mice, has suggested developmentally controlled nonrandom use of V(D)J genes and unique patterns of junctional diversity (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). With better understanding of BCR signaling, recent studies have provided direct evidence that bias in the Ab repertoire is a result of selection mediated through pBCR and BCR (18 -20).…”
mentioning
confidence: 99%
“…In the rearrangement of the IgH gene, the usage of J H segments revealed a developmental stage-specific trend. [7][8][9][10][11][12][13] At the earliest stage of B cell development, the initial D-J H rearrangements predominantly occur between D H Q52 and J H -1 segments which are located close to each other. 53 During B cell development, a second or a third D-J H joining might occur, then the more 5ЈD segments and more 3ЈJ H segments would join at a later stage.…”
Section: Figurementioning
confidence: 99%
“…6 Studies on IgH variable region gene sequences at various stages of development have revealed stage-specific trends in the usage of V H , D, and J H segments, the degree of N nucleotide addition, and the rate of somatic mutations. [7][8][9][10][11][12][13] However, little is known of the organization and diversification of the IgL variable region gene on -chain. On the other hand, multiple myeloma (MM) has a variety of clinical features relating to clinical stage, prognosis and complication.…”
Section: Introductionmentioning
confidence: 99%
“…8 Furthermore, the post-BMT immune deficiency may be explained by a restricted usage of the Ig genes, as seen in fetal and neonatal life. [9][10][11] The genes encoding the variable and constant region of the Ig heavy chain (IgH) are located on chromosome 14q. Variability in the antigen binding site is obtained by recombination of one diversity (D) gene to one junctional (JH) gene, and a second recombination of this complex to a variable (VH) gene segment.…”
mentioning
confidence: 99%